A partnership transformed three decades of cooperation between the Asian Development Bank and the People Republic of China in support of reform and opening up. - Wihtol, Robert (Asian Development Bank, 2018)
This publication explores three decades of cooperation between the Asian Development Bank and the People Republic of China in support of reform and opening up.